If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 5 + 3t Solving 3 = 5 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 3 + -3t = 5 + 3t + -3t Combine like terms: 3t + -3t = 0 3 + -3t = 5 + 0 3 + -3t = 5 Add '-3' to each side of the equation. 3 + -3 + -3t = 5 + -3 Combine like terms: 3 + -3 = 0 0 + -3t = 5 + -3 -3t = 5 + -3 Combine like terms: 5 + -3 = 2 -3t = 2 Divide each side by '-3'. t = -0.6666666667 Simplifying t = -0.6666666667
| 2x-8=12+3x | | 4x+18-6x+38= | | 0=2t^2-13t+21 | | k+5=4k-10 | | -2x+4=-14 | | (5x^2-7x+7)*(6x+9)=0 | | Y+5=4y-10 | | 7+2s-6=6s+8-3s | | 9x^2-34x-8=0 | | 13t-48=2+14t | | 5-2x=-5 | | 3z+15=27 | | 16x^2-320=88x | | 4x-8=12+3x | | 4x^2-2x-9=7x+8 | | 2(4x-3)-=4+2x | | 3z+17=27 | | 8a=3a+35 | | 6y-7=-2y+13 | | x(x+2)=168 | | 4x^2+47x+78=0 | | 15=b-5 | | 3+5n=16 | | -4+3x=-4 | | .3x=140+x | | .8333v+1.5=.875v+1.666 | | 2x^2+6x+9=225 | | (-4)=2x+5 | | 15=b-9 | | -6x-4=-10 | | 4(7x+8)+2=28x+34 | | 7x-2=2x+18 |